If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2g + 4(3 + -1g) = 5g + 19 2g + (3 * 4 + -1g * 4) = 5g + 19 2g + (12 + -4g) = 5g + 19 Reorder the terms: 12 + 2g + -4g = 5g + 19 Combine like terms: 2g + -4g = -2g 12 + -2g = 5g + 19 Reorder the terms: 12 + -2g = 19 + 5g Solving 12 + -2g = 19 + 5g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-5g' to each side of the equation. 12 + -2g + -5g = 19 + 5g + -5g Combine like terms: -2g + -5g = -7g 12 + -7g = 19 + 5g + -5g Combine like terms: 5g + -5g = 0 12 + -7g = 19 + 0 12 + -7g = 19 Add '-12' to each side of the equation. 12 + -12 + -7g = 19 + -12 Combine like terms: 12 + -12 = 0 0 + -7g = 19 + -12 -7g = 19 + -12 Combine like terms: 19 + -12 = 7 -7g = 7 Divide each side by '-7'. g = -1 Simplifying g = -1
| x+x+1+x+2+x+3=-15 | | 4x+25=2x+49 | | 4x+36y=-12graph | | 2x+8(x-2)=4x-3(3-2x)-7 | | 3+3x=-7+x | | 6x-3(2x-4)+1=13 | | 15-4x+30=7-x | | 4+12+x=4+6+2x | | -0.01x^2+1.8x-106=0 | | 3+55x=33x+9 | | 4x+7=6x-19 | | (5y+9)+y= | | 11.8-0.4x+3.6=40 | | 25-2(4x+15)=51 | | -13+2x=-39+24x | | 25.00(x+5.00)=425.00 | | 5000=150+400 | | 32-3x=11-2x | | 10+3x=-6x-98 | | 3x^2+8x-91=0 | | 3(x+4)-5x=72 | | 65+900+b=1053 | | 5.87b=8.68+3.68b | | (19-X)-(18-X)=3 | | 16=4(x-2) | | n^2-10n-88=8 | | 3(5-x)=2(1+x) | | 6y=5x+60 | | 4x^2-17x+34=6x+6 | | 2n^2+5n-33=12 | | 19x-18x=3 | | x+3x+3x+5=166 |